Plant Growth Promotion Under Water: Decrease of Waterlogging-Induced ACC and Ethylene Levels by ACC Deaminase-Producing Bacteria - Ali, Sajid; Kim, Won-Chan (Frontiers in Microbiology, 2018)
Some plant growth-promoting bacteria encode for 1-aminocyclopropane-1-carboxylate (ACC) deaminase, which facilitates plant growth and development by lowering the level of stress ethylene under waterlogged conditions. The substrate ACC is the immediate precursor for ethylene synthesis in plants; while bacterial ACC deaminase hydrolyzes this compound into α-ketobutyrate and ammonia to mitigate the adverse effects of the stress caused by ethylene exposure. Here, the structure and function of ACC deaminase, ethylene biosynthesis and waterlogging response, waterlogging and its consequences, role of bacterial ACC deaminase under waterlogged conditions, and effect of this enzyme on terrestrial and riparian plants are discussed.